2022
DOI: 10.3390/cancers14205122
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Cu(I)-Chelator with Potential Anti-Tumorigenic Action—A Proof-of-Principle Experimental Study of Human H460 Tumors in the CAM Assay

Abstract: Human lung cancer ranks among the most frequently treated cancers worldwide. As copper appears critical to angiogenesis and tumor growth, selective removal of copper represents a promising strategy to restrict tumor growth. To this end, we explored the activity of the novel high-affinity membrane-permeant Cu(I) chelator PSP-2 featuring a low-zeptomolar dissociation constant. Using H460 human lung cancer cells, we generated small tumors on the chorioallantoic membrane of the chicken embryo (CAM assay) and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We furthermore demonstrated a significantly improved vascularization in presence of ZnO NPs. Using the CAM assay, a typical model system to study angiogenesis [ 48 , 50 , 51 , 56 , 59 ], we compared four groups with different concentrations of ZnO NPs, constructed from two different NP sizes (A = 25 nm, B = 70 nm) and two different sonocoating times (0.5 or 1 s), to the plain PDLLA/PLGA biopolymer scaffold. Previous studies have shown the angiogenic properties of ZnO NPs by analyzing the CAM and CAM-scaffold interface vessels [ 20 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We furthermore demonstrated a significantly improved vascularization in presence of ZnO NPs. Using the CAM assay, a typical model system to study angiogenesis [ 48 , 50 , 51 , 56 , 59 ], we compared four groups with different concentrations of ZnO NPs, constructed from two different NP sizes (A = 25 nm, B = 70 nm) and two different sonocoating times (0.5 or 1 s), to the plain PDLLA/PLGA biopolymer scaffold. Previous studies have shown the angiogenic properties of ZnO NPs by analyzing the CAM and CAM-scaffold interface vessels [ 20 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of copper has led to inferior angiogenic responses in rabbit models [ 134 ]. These findings concerning copper's proangiogenic effects have led scientists to develop treatments to inhibit copper in cancers through chelation to inhibit vascularization and metastasis [ 129 , 135 ]. For example molybdenum in tetrathiomolybdate (TTM) has been proven to chelate copper, resulting in antiangiogenic effects [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demcisakova et al analyzed the vascularization potential of biomaterial scaffolds that were positioned on the CAM as a test model for novel bone repair materials [3]. Heuberger et al reported that the potential anti-cancer effect of copper chelators was mostly mediated through angiosuppression [4]. Faihs et al introduced the application of a novel image analysis software for angiogenesis research [5].…”
Section: Survey For Papers In This Special Cam Issuementioning
confidence: 99%